Six new species of deep water Ampeliscidae (Crustacea: Amphipoda) from Brazilian Coast - Valério-Berardo, Maria Teresa (Zootaxa, 2008)
Six new species of the family Ampeliscidae Costa, 1857 are described from Campos Basin Deep Sea in Brazilian Cost. The four new species of the genus Ampelisca herein described, Ampelisca wakabarae sp. nov., Ampelisca campensis sp. nov., Ampelisca anae sp. nov., Ampelisca minuta sp. nov. raised the total number of species of this genus recorded along the Brazilian coast to 14. Others species described are: Byblis bjornbergae sp. nov. and Haploops meloi sp. nov. These are first records of these genera for Brazilian coast. A key to the species of the family Ampeliscidae recorded from Brazilian coast is provided.